2017
DOI: 10.18488/journal.ar.2017.41.8.20
|View full text |Cite
|
Sign up to set email alerts
|

Role of Probiotics in Animal Nutrition

Abstract: Article HistoryThe anaerobic probiotic technology (ZAD) is a patented technique. The products are in two forms either liquid or powder. The powder products are coated so it can handle the pressure and the temperature of the extruders. They are fed as follows; 10 gm/head /day for large animals or 1 kg/ tone of fed (for ZADO). In case of Liquid (ZAD); it is fed 10 ml/head/day for large animals and 1.5 ml liter for poultry and rabbits. It decreases the aflatoxins less than 11% by inclusion rate of 7% of ZAD in 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…The concentration of acetic acid generated from the caecum content of rabbit's administration orally ZAD ® there were also higher numeric values for probiotics. This agreed with previous findings Gado et al (2017) who showed that inclusion of the ZADO ® treatment has been increased (P≤0.05) the rumen ammonia N and total VFA concentrations before and 3 h post-feeding.…”
Section: Caecum Activitysupporting
confidence: 93%
See 4 more Smart Citations
“…The concentration of acetic acid generated from the caecum content of rabbit's administration orally ZAD ® there were also higher numeric values for probiotics. This agreed with previous findings Gado et al (2017) who showed that inclusion of the ZADO ® treatment has been increased (P≤0.05) the rumen ammonia N and total VFA concentrations before and 3 h post-feeding.…”
Section: Caecum Activitysupporting
confidence: 93%
“…The present results agree with experiments in pre-mature Hy-Plus rabbit reported by Gado and Salem (2014), where ZADO ® up to 5 g/kg diet has been inserted without weakening performance. Additionally, Gado et al (2017) confirmed that a mixture of enzymes obtained from anaerobic bacteria present in ZAD ® had a beneficial effect to converts the polysaccharide into monomers by the enzyme catalytic process in growing rabbits. Besides, Bhatt et al (2017) showed that supplementation in rabbit diets of probiotics (107 CFU/g concentrate) Lactococcus lactis and Lactobacillus acidophilus increased (P≤0.05) the gain of weight (24.5 vs. 22.5 g/d) as compared with the control group.…”
Section: Growth Performancementioning
confidence: 67%
See 3 more Smart Citations